Extrapontine myelinolysis manifested selectively by acute severe parkinsonian syndrome. Case Report - Stetkarova, IIvana; Svobodova, Zuzana; Soltez, Jozef; Svatova, Jinda (Neuro endocrinology letters, 2016)
OBJECTIVES: Osmotic demyelination syndrome (ODMS) is a rare and serious neurologic disorder with acute myelin disintegration, usually in the pontine area (central pontine myelinolysis) and to a lesser extent, even in other areas of the central nervous system (extrapontine myelinolysis). The main underlying mechanism is the change of serum osmolality with quick correction of low mineral levels, mainly hyponatraemia. Clinical manifestation is various and depends on the localization. DESIGN: We describe an acute isolated extrapontine myelinolysis causing acute onset of parkinsonism in a 61-year-old man who developed quickly progressing parkinsonian syndrome after the rapid correction of hyponatraemia. RESULTS: Brain MRI revealed lesions only in the striatum, sparing the globus pallidus. Substitution therapy with high doses of levodopa significantly improved his clinical condition. CONCLUSION: Extrapontine myelinolysis with isolated affection of basal ganglia is extremely rare. In such case, clinical manifestation of acute severe parkinsonism could be successfully treated by high dose of levodopa.
Keywords: Myelinolysis, Central Pontine; výsledek terapie; Middle Aged; mužské pohlaví; bazální ganglia; hyponatremie; magnetická rezonanční tomografie; Magnetic Resonance Imaging; Basal Ganglia; Humans; Acute Disease; Parkinsonian Disorders; centrální pontinní myelinolýza; Hyponatremia; parkinsonské poruchy; lidé středního věku; akutní nemoc; Treatment Outcome; lidé; Male